Heat Stability of Red Fruit Extract (Pandanus conoideus) Color as Potential Source of Natural Pigments - Satriyanto, Budi; Widjanarko, Simon B.; Yunianta, Yunianta (Jurnal Teknologi Pertanian, 2012)
The most important nutritional component in red fruit Pandanus conoideus is pro-vitamin A in the form of Î²-carotene. Î²-carotene is a non polar, long-chained carbon organic compound. Extraction of red fruitâ€™s oil in volves thermal process on boiling phase. Î²-carotene is unstable at high temperatures, so the red fruitâ€™s oil quality may decrease on in appropriate heating temperature and duration. The purpose of this research were to determine the effects of extraction time by boiling at 85 â°C to the pigment quality of red pandanus fruit extractâ€™s oil (RFOP). Experiments were performed by Completely Randomized Design (CRD) with single factor, heating duration (60 minutes, 120 minutes, 180 minutes, 240 minutes, 300 minutes and 360 minutes). Research results showed that heat-extraction time in optimum temperature would affect on total carotenoids and Î²-carotene content of RFOP so that stability of pigmentâ€™s color was optimal and stable. Treatments also affect moisture content, yield and color L*, a *, b*. Extraction time that provide the best results was 360 minutes at 85 â°C. GCMS analysis showed the dominant compounds of RFOP were heptadecene-(8)-carbonic acid (79.66%), and hexadecanoic acid (5.62%).Â Keywords: Î²-carotene stability, heating effect, color intensity, Papua local potential, red fruit GCMS chromatogram